2020
DOI: 10.24191/jmeche.v17i2.15301
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Process Parameters in Wire and Arc Additive Manufacturing (WAAM) Process

Abstract: Wire and arc additive manufacturing (WAAM) has developed a wide range of processes and applications. This technology is a new approach to modern manufacturing and is gaining interest from the research community due to its ability to create affordable, large-scale components. Nevertheless, WAAM may affected by porosity, humping and undercut. These issues need to be addressed in a specific way to achieve desired quality that is comparable to the traditional processing technique. This article examines various wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
(9 reference statements)
1
6
0
Order By: Relevance
“…The bead height was found to increase with the increasing the WFR. A similar result was observed in Figure 6(b) when Rosli et al [57] measured the height of three WAAM beads deposited at three different WFR at eight different points along the bead length, other parameters were kept constant. As shown in Figure 7, the parametric study on WAAM–GMAW of thin wall 308L stainless steel conducted by Le et al [58] revealed that the bead height decreased with increasing the traverse speed.…”
Section: Processing Parameters and Waam Bead Qualitiessupporting
confidence: 82%
See 2 more Smart Citations
“…The bead height was found to increase with the increasing the WFR. A similar result was observed in Figure 6(b) when Rosli et al [57] measured the height of three WAAM beads deposited at three different WFR at eight different points along the bead length, other parameters were kept constant. As shown in Figure 7, the parametric study on WAAM–GMAW of thin wall 308L stainless steel conducted by Le et al [58] revealed that the bead height decreased with increasing the traverse speed.…”
Section: Processing Parameters and Waam Bead Qualitiessupporting
confidence: 82%
“…
Figure 6 Variation of the bead height with the WFR using (a) WAAM–GTAW [56] and (b) WAAM–GMAW techniques (Adapted with permission from ref. [56,57]).
Figure 7 Main effects plot for bead height for WAAM–GMAW of thin wall 308L stainless steel. I = current, U = voltage and V = traverse speed.
…”
Section: Processing Parameters and Waam Bead Qualitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Deposition parameters [110], heat input, Interlayer temperature, and the duration of interlayer pauses were significant factors influencing the formation and distribution of pores in aluminum 5183 alloys printed in the WAAM process [111]. Similarly, different welding travel speeds at which defects become noticeable also imply both wire feed speed and travel speed in the welding process [112]. In contrast, substrate (bed or baseplate) thickness was found to have a major influence on the RS distribution along deposit height.…”
Section: Factors Influencing Rs In Waammentioning
confidence: 99%
“…Thus, the most common factors of WAAM products' defects are the process parameters, which limit the acceptance of this technology [120][121][122][123][124]. In another way, undercut and humping are the common defects found in the WAAM products with the major influence of deposition height, width, and stable layer is produced heat input per length values [112].…”
Section: Factors Influencing Rs In Waammentioning
confidence: 99%